2019
DOI: 10.1111/jfbc.12843
|View full text |Cite
|
Sign up to set email alerts
|

Soy husk extract improves physical and biochemical parameters of obese–diabetic rats through the regulation of PPARγ expression

Abstract: Unhealthy eating habits and lack of physical activities are among the contributing factors for obesity and diabetes. It has been reported that consumption of naturally occurring phenolics could exert beneficial effects toward these diseases. Therefore, this study aims to evaluate the ability of phenolic‐rich soy husk powder extract (SHPE) in modifying the physical and biochemical parameters for obesity and diabetes. Forty‐nine Sprague Dawley rats were divided into seven groups, including three supplementary/tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…As SHPE has been reported to contain a significant amount of gallic acid and chlorogenic acid (Appendix 2) (Tan et al , 2010), it can be postulated that the anti-adipogenic properties of soy husk was derived from these two bioactive compounds. A recent study by Tan et al (2019) showed that soya bean husk extract improved the physical and biochemical parameters of obese-diabetic rats through the regulation of PPAR γ expression. It appears that in vitro findings derived from the present study are in well-agreement with those reported in an obese-diabetes rat model.…”
Section: Discussionmentioning
confidence: 99%
“…As SHPE has been reported to contain a significant amount of gallic acid and chlorogenic acid (Appendix 2) (Tan et al , 2010), it can be postulated that the anti-adipogenic properties of soy husk was derived from these two bioactive compounds. A recent study by Tan et al (2019) showed that soya bean husk extract improved the physical and biochemical parameters of obese-diabetic rats through the regulation of PPAR γ expression. It appears that in vitro findings derived from the present study are in well-agreement with those reported in an obese-diabetes rat model.…”
Section: Discussionmentioning
confidence: 99%
“…Given the many drawbacks of the available antidiabetic drugs, patients are looking for a safer and cheaper alternative for the treatment of diabetes mellitus. A growing body of literature recognizes the use of natural products from herbs and fruits (Adyab et al, 2019;Oyeleye et al, 2021;Tan et al, 2019;Teoh & Das, 2018). These plant extracts contain numerous active metabolites that synergistically work to reduce blood glucose and improve other metabolic complications related to diabetes mellitus (El-Abhar & Schaalan, 2014;Kar et al, 2003;Lasano et al, 2021).…”
mentioning
confidence: 99%